2010
DOI: 10.1111/j.1475-6773.2010.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hospital Compare Mortality Model and the Volume–Outcome Relationship

Abstract: Objective We ask whether Medicare’s Hospital Compare (HC) random effects (RE) model correctly assesses AMI hospital mortality rates when there is a volume-outcome relationship. Data Sources/Study Setting Medicare claims on 208,157 AMI patients admitted in 3,629 acute care hospitals throughout the U.S. Study Design We compared average adjusted mortality using logistic regression to average adjusted mortality based on the Hospital Compare RE model. We also fit RE models with the same patient variables as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 28 publications
4
81
0
Order By: Relevance
“…Silber et al 15 have demonstrated that models that ignore volume effects are highly unlikely, by design, to ever identify low-volume centers as outliers, a result that we have duplicated in our findings. 15 As prior reports suggest a clinically significant volume-outcome relationship for CAS, 24 we chose to include hospital volume in our risk-standardization models.…”
Section: Modeling Issuessupporting
confidence: 80%
See 2 more Smart Citations
“…Silber et al 15 have demonstrated that models that ignore volume effects are highly unlikely, by design, to ever identify low-volume centers as outliers, a result that we have duplicated in our findings. 15 As prior reports suggest a clinically significant volume-outcome relationship for CAS, 24 we chose to include hospital volume in our risk-standardization models.…”
Section: Modeling Issuessupporting
confidence: 80%
“…It is possible that the inclusion of hospital variables more specific to CAS outcomes might provide better discrimination between hospitals. Silber et al 15 demonstrated the critical importance of including hospital-level predictors in the Hospital Compare method of investigating risk-standardized outcomes, and in fact, our study revealed several hospital factors that were independent predictors of adverse outcomes. As hospitals are currently required to report structural characteristics to Medicare in the course of obtaining CAS recertification, this may be an ideal mechanism for collecting data that could be incorporated in a more detailed hospital-level mortality model.…”
Section: Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Very few hospitals were identified as having mortality that differed from the national rate (99.5 percent were labeled as having heart attack mortality that was no different than the national rate). 15 Thus, this report was unlikely to influence patients' or hospitals' behavior. Hospital Compare reported hospitalspecific levels of mortality performance in 2008; however, the introduction of this mortality reporting was too late in our study period to make a practical difference in our results.…”
mentioning
confidence: 82%
“…Although there is very little data about any one small hospital, hence very little data to check a statement about one small hospital, there is plenty of data about small hospitals as a group. When Hospital Compare's predictions for all small hospitals are added up, it is unambiguously clear that the risk at small hospitals as a group is well above the national average; see Silber et al (2010).…”
Section: Individualized Bayes Predictions Should Calibrate With Soundmentioning
confidence: 99%